Ethical On Societal Challenges Dalam Aplikasi Bisnis Di Social Media (Sosmed) - Imam Sangputra; Nurul Asifah (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
This study aims to identify the importance of ethics in doing business using various social media applications that should be able to provide benefits to MSMEs who do business through social media. In social media, it is easy to do business in it openly and known to the public by showing various forms of business. Ethical businessmen are highly expected by consumers in offering goods/services so that they can satisfy and provide trust in consumers. The existence of events in ethics in social media is the ease of communication, reducing prices according to the form of products, business independence, and empowerment in doing business. The method used is the Library method which uses primary data which is seen from books, journals, and the web about ethical challenges in the good use of social media which can be used as a reference for this writing. With a relatively good discussion in accepting ethical social challenges that must be carried out in doing business in an efficient way in the form of User date Privacy, Manipulation and Misinformation, Spread of Hatred and Discrimination, Impact on Mental Health, Economic Exploitation, Authenticity and Transparency.